Converting maize production with low emergy cost and high economic return for sustainable development. (February 2021) - Wang, Xingya; Tan, Weiming; Zhou, Shunli; Xu, Yang; Cui, Tao; Gao, Hong; Chen, Mingli; Dong, Xuehui; Sun, Hongyong; Yang, Jinzhong; Wu, Yongcheng; Kong, Fanlei; et al.
Abstract: Promoting more sustainable agriculture while simultaneously meeting the increased demands for food due to the growing population is a great challenge in the 21st century. Here we addressed this challenge by conducting on-farm field experiments at 40 sites across the broad aro-ecological maize region in China during 2017–2018. According to a modern understanding with emergy and economic aspects, a set of new variety-based low emergy system was developed. Compared with the current traditional farmers' system, the new system improved the sustainability (emergy sustainability index) by 19% and increased economic return by 47% while similar productivity (maize yield) was achieved. More than 80% of the modeled yield potential was realized. Moreover, the decrease of nonrenewable materials input in the new system contributed to 88% of the sustainability improvement. As food and resource concerns become more severe in many global regions, this new system is likely to supply a typical case and could be adopted widely to realize the United Nations Sustainable Development Goals (SDGs) in agricultural transformation. Highlights: The sustainability (ESI) was improved by 19% in the new system. The total economic return was increased by 47% in the new system. Compared with the CS, similar grain yield was achieved in LES. The decrease of nonrenewable materials contributed to 88% of improved ESI. Crop production will be more sustainable by decreasing nonrenewable materials.